O FUNKCJI STYLISTYCZNEJ WYPOWIEDZENIA - Kiklewicz, Aleksander (Acta Neophilologica, 2007)
The article discusses problems of the social distinctness of natural languages (on example of Polish language and Russian). According to the author, stylistic function is one of basic functions of sentence, and namely consists in the subordinating of the form, structure and content of sentence, the definite communication context and, first of all, the definite social groups as well as definite types of social reports. The manifesting of the stylistic function with the help of specialized, on example, lexical, expressions is the norm of linguistic communication. The author considers two basic notions of sociolinguistics: the functional styles and the social variants of language (the sociolects), and beyond this the related notion - the species of text. The structure of stylistic function according to the author consists with two meanings: the participants’ profile as well as the profile of contact. First meaning has four changes: regional, biological, and individual. In range „the profile of contact” it distinguishes two detailed meanings: contact „the man - the man” and contact „the man - the text”. The author distinguishes nine types of contacts of this second kind: scientific, productive, didactic, administrative, medial, advertising, sacred, artistic and common. Near the two stylistic parameters (the participants’ profile as well as the profile of contact) the author in axiomatic way distinguishes and describes four kinds of sentence and texts: a) the participants’ profile +, the profile of contact +; b) the participants’ profile +, the profile of contact -; c) the participants’ profile -, the profile of contact +; d) the participants’ profile -, the profile of contact -.